Investigation of Reactions Involving Pentacoordinate Intermediates The Mechanism of the Wittig Reaction - Byrne, Peter A. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2012)
In this thesis, the author outlines the discovery of an effect common to representative examples of all Li salt-free Wittig Reactions. The implications of such a universally applicable effect are that all such Wittig reactions occur through the same mechanism. Although the Wittig reaction was first discovered in 1953, its reaction mechanism has never been definitively settled with many different variants proposed and disproved. The work in this thesis shows conclusively that for [2+2] cycloadditions all Wittig reactions occur by the same irreversible mechanism. In addition, the author also describes a new chromatography-free method for the removal of phosphine oxide from the alkene crude product of the Wittig reaction. The work in this thesis has led to several publications in high-profile journals.